Differences in the fitness effects of traded resources shape traits and persistence in multi-mutualist communities - Renuka Agarwal; Anne E. Curé; Kari A. Segraves; David M. Althoff (PLoS ONE, 2026)
Mutualistic interactions, where species reciprocally benefit from each other, are crucial for ecosystem stability and biodiversity. These interactions often involve species that experience different fitness effects for the traded resources or services. Because mutualisms rely on positive feedback between partners, such asymmetries can strongly influence evolutionary outcomes. Differences in fitness effects create divergent selective pressures, shaping trait evolution and determining the persistence of mutualisms. The strength of these effects can also vary depending on the availability of traded resources from other sources. Despite their importance, the evolutionary role of fitness asymmetries in mutualism has received little attention, beyond recognizing that some species may be more dependent on their partners than others. This study investigates how asymmetry in the fitness effects of a traded resource influences the persistence and phenotypic trait evolution of species in multi-mutualist guilds. To test this, we constructed synthetic multi-mutualist communities by combining, reproductively isolated and genetically modified strains of Saccharomyces cerevisiae that engage in a nutritional mutualism by trading adenine and lysine. One guild of four strains cannot produce lysine but overproduces adenine while the other guild cannot produce adenine but overproduces lysine. Lysine overproducers survive periods of low adenine better than adenine overproducers survive low lysine. Over a four-week evolution experiment we observed that strain persistence was strongly influenced by the availability of external resources. Communities in media containing traded resources supported the survival of all strains, whereas obligate conditions led to a significant extinction, especially for adenine overproducers. We observed distinct evolutionary trajectories of traits under obligate versus supplemented conditions. Phenotypic assays revealed that costs and benefits evolved differently depending on the essentiality of the traded resource and nutrient supplementation. These results demonstrate that asymmetries in the fitness effects of traded resources can influence evolutionary outcomes, species persistence, and community stability in multi-mutualist communities.